Primary small cell carcinoma with neuroendocrine properties of the mandible: A case report and literature review - Yue Chen; Chi Wang; Hui-ming Wang; Jun Li; Hui-yong Zhu (Elsevier, 2017)
Small-cell carcinomas at extrapulmonary primary sites are rare but they have been documented to arise at various locations. We report a case of small-cell carcinoma arising in the mandible, which has so far not been reported in the literature. A 37-year-old male patient underwent partial resection of the left mandible and adjuvant chemotherapy. Immunohistochemistry confirmed the diagnosis of small-cell carcinoma with neuroendocrine properties. The patient has been free of disease for 18 months after receiving treatment and was alive at the time of writing. We recommend surgical resection followed by chemotherapy for managing small-cell carcinomas in the mandibular region. Keywords: chemotherapy, immunohistochemistry, mandible, neuroendocrine system, small cell carcinoma